Desenho, fala e escrita da criança: formas de desenvolvimento social - Santos, Flanciélle Pereira Pracidono (Universidade Federal do Tocantins, 2022)
This research was the theme of the child's drawing, speech and writing: forms of social development. The general objective was to understand the contribution of drawing, speech and writing to the child's social development, and the specific objectives were: to present the child's social formation from Vygotsky; discuss the relationship of the child with his/her speech-mediated design; analyze the development of the drawing and the writing of the child. This research is justified by the need to understand how drawing being something natural of the child's development can be used as a tool for the development of writing and is associated with the child's speech. In this sense, do we have the problem of this research to understand how drawing, speech and writing contribute to the child's social development? The methodology used the qualitative approach, of basic exploratory nature, with a bibliographic review procedure based on scientific studies. We base the research based on the studies of authors such as Vygotsky (1994); Iavelberg (2013); Derdyk (1989); Méredieu (2006) among others. The studies conducted by these authors contribute to the understanding of the child's design. Thus, it was possible to understand that in addition to a playful activity, the child's drawing is related to speech and contributes to writing and social development.